Ppm1d truncating mutations promote the development of genotoxic stress-induced AML - Burocziova, Monika; Danek, Petr; Oravetzova, Anna; Chalupova, Zuzana; Alberich-Jorda, Meritxell; Macurek, Libor (Leukemia, 2023)
Hematopoietic stem cells (HSCs) ensure blood cell production during the life-time of an organism, and to do so they need to balance self-renewal, proliferation, differentiation, and migration in a steady state as well as in response to stress or injury. Importantly, aberrant proliferation of HSCs leads to hematological malignancies, and thus, tight regulation by various tumor suppressor pathways, including p53, is essential. Protein phosphatase magnesium-dependent 1 delta (PPM1D) is a negative regulator of p53 and promotes cell survival upon induction of genotoxic stress. Truncating mutations in the last exon of PPM1D lead to the production of a stable, enzymatically active protein and are commonly associated with clonal hematopoiesis. Using a transgenic mouse model, we demonstrate that truncated PPM1D reduces self-renewal of HSCs in basal conditions but promotes the development of aggressive AML after exposure to ionizing radiation. Inhibition of PPM1D suppressed the colony growth of leukemic stem and progenitor cells carrying the truncated PPM1D, and remarkably, it provided protection against irradiation-induced cell growth. Altogether, we demonstrate that truncated PPM1D affects HSC maintenance, disrupts normal hematopoiesis, and that its inhibition could be beneficial in the context of therapy-induced AML.
Keywords: Mice; Leukemia, Myeloid, Acute; nádorový supresorový protein p53; poškození DNA; DNA Damage; mutace; akutní myeloidní leukemie; Animals; Mutation; zvířata; proliferace buněk; myši; Cell Proliferation; Tumor Suppressor Protein p53